Influence of Elevated Body Mass Index on Lipid Metabolism and Glycemic Regulation in Type 2 Diabetes Mellitus. A Comparative Analysis - Mohsin Shafi, Akhtar Hussain, Saima Iram, Amina Ijaz, Mumtaz Ali Lakho, Qamar Yasmeen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease that is strongly associated to obesity, and this leads to exacerbation of insulin resistance and changes in lipid metabolism. High body mass index (BMI) has been related with defects in glycemic regulation and dyslipidemia, making the cardiovascular risk higher. Objectives: The purpose of this study was to determine if elevated BMI impacts glycemic indices and lipid profiles in T2DM patients. It also aimed to explore the effect of other demographic factors like age, sex, duration of diabetes, educational level, urban/rural residency, physical activity, and socioeconomic status. Methods: From January 2022 to December 2022, a cross-sectional study was conducted at Liaquat University of Medical & Health Sciences (LUMHS), Jamshoro, Pakistan. In total, 100 T2DM patients were stratified into 3 groups according to BMI: normal weight (BMI 18.5–24.9 kg/m²), overweight (BMI 25–29.9 kg/m²), and obese (BMI ≥30 kg/m²). Blood samples were taken fasting to measure the glycemic indices (fast blood glucose and HbA1c) and lipid profile parameters (total cholesterol, LDL, HDL, and triglycerides). Also recorded were demographic and clinical data. ANOVA and multivariate regression were performed on statistical analysis, with a significance at p < 0.05. Results: Fasting blood glucose (145 ± 15 mg/dL) and HbA1c (8.5% ± 0.7%) were significantly higher in obese (p < 0.001) than normal weight (120 ± 10 mg/dL and 7.2% ± 0.5%, respectively) and overweight (130 ± 12 mg/dL and 7.8% ± 0.6%, respectively) patients. Total cholesterol (210 ± 20 mg/dL), LDL (130 ± 15 mg/dL), and triglycerides (200 ± 25 mg/dL) were markedly elevated, HDL (40 ± 5 mg/dL) was reduced, and all (p < 0.001) compared to other groups. The demographic data also revealed that obese patients had a longer duration of diabetes, a lower level of education, and lower physical activity. Conclusions: In T2DM patients, elevated BMI is associated with worse glycemic control and more atherogenic lipid profile. As a result, these findings underscore the necessity of combining weight management and lifestyle modifications with other components of the comprehensive treatment of T2DM aimed at a reduction of the cardiovascular risk. Keywords: Type 2 diabetes mellitus, body mass index, glycemic control, dyslipidemia, obesity, cardiovascular risk, lipid metabolism.